CURRENT TREND IN RESEARCH ABOUT INVISALIGN® SUCCESS OUTCOME: A SYSTEMATIC REVIEW USING PRISMA GUIDELINE - Zakyah, Akhyar Dyni; Laviana, Avi (Faculty of Dentistry, Universitas Islam Sultan Agung, 2021)
ABSTRACTBackground: While some researches have claimed that Invisalign® is successful in creating meaningful tooth movement, there is still no comprehensive literature review that summarizes them using one valid and reliable parameter. American Board of Orthodontics-Model Grading System (ABO-MGS) is an objective measurement for the success of orthodontic treatment. This systematic review is determined to provide scientific pieces of evidence to prove the truth of the claim using ABO-MGS. Method: English-based health sciences journal databases were searched using